(untitled) (Revista Cientifica Ingenio Magno, 2019)
From different occupations that are applied in the professions, it is found that each one fulfills the important social development, the economists determine the behavior of dif- ferent economic forces that affect the stock market, the lawyers defend the rights of the large, medium and small entities, such as the rights of each citizen, the architects with their creativity beautify the cities, with the health areas it is clear the responsibility established to know the people importance, therefore their physical integrity. The engineer promotes with his or her profession toward the construction of elements that contribute to increase the life people level, for example, the civilian contrib- utes with his or her knowledge in infrastruc- ture construction to achieve a safe housing environment, the mechanic creates impres- sive functional designs that diminish manual labor of people. In addition, we could say with great certainty of about the social contribution that each engineering does. however, in this reflection the role of the profession of elec- tronic engineering is briefly showed, in the same way the present and future impact it will have on the society. We begin by giving a quick look at the histo- ry of inventions to find the path of the elec- tronical evolution, from the study carried out by William Crookes, on the electrical charges in gases, which subsequently lead Wilhelm Conrad Roentgen to the discovery of radiations and later that of x-rays, which were carried out by the couple of Scientists Marie and Pierre Curie. on the other hand, some other illustrious scientists focus their attention on other fields of electronics knowledge, they were the physicists Max- well and Hertz who opened the way to the communications area with the discovery of electromagnetic radiation. But it was Thom- as Alva Edison with the invention of the light bulb, who started the way to the first stages to make homes confortable and in general the populations. But the discovery considered a fundamental axis that started changes today and, in the future, it was the invention of a transistor, a device that the IBM company has been able to build with a size of 5 nanometers length, smaller than the diameter of the tip of a pin. as a result of the development of this technology, levels of automation are established and they are rang- ing from a simple control "on" or "off", to the revolutionary devices that large companies put in our hands "cell phones". But now we have a question, how far can the technological advance of electronics go? In this regard, it is essential to observe in our environment the different fields that permeate our lives, in the field of health, we will find that who will perform the surgeries will no longer be a surgeon, instead it will be assisted by a robotic system; the sporting events will be seen in third dimension, the big distribution market chains will already have the informa- tion about the food that is missing or left over at homes, only with a simple click on the cell